2022
DOI: 10.1186/s12978-022-01330-z
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal depression in Sri Lanka: a qualitative study of public health midwives’ views and practices

Abstract: Background Almost all pregnant people in Sri Lanka receive antenatal care by public health midwives. While there is strong infrastructure in Sri Lanka for postpartum mental health care, the current practices within antenatal mental health care have not been externally evaluated. The purpose of this study is to investigate the current clinical guidelines and experiences of how public health midwives diagnose and treat antenatal depression. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Midwives can help with therapy by talking to a psychiatrist and monitoring pregnant women. The midwife is a major role in the follow-up of treatment, making home visits after the treatment begins to examine the mother in their care (Wyatt et al, 2022). Treatment for mothers diagnosed with perinatal anxiety was noted to be irregular even interprofessional communication proved difficult (Silverwood et al, 2019).…”
Section: Results Article Characteristic Based On Research Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Midwives can help with therapy by talking to a psychiatrist and monitoring pregnant women. The midwife is a major role in the follow-up of treatment, making home visits after the treatment begins to examine the mother in their care (Wyatt et al, 2022). Treatment for mothers diagnosed with perinatal anxiety was noted to be irregular even interprofessional communication proved difficult (Silverwood et al, 2019).…”
Section: Results Article Characteristic Based On Research Designmentioning
confidence: 99%
“…Based on the research in Sri Lanka, the midwife has delivered antenatal education to almost all pregnant women, and it has well developed infrastructure for mental health care for postpartum. However, the care practice of antenatal mental health has been not evaluated independently (Wyatt et al, 2022). In this study, 12 midwives have varied awareness level about prenatal depression and there is no diagnosis pattern, but it is consistent in midwife clinical procedures, following guidelines for referral and case management follow-up, and developing excellent relationships.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…However some midwives may consider screening for antenatal depression to be too demanding and requiring too much effort [14] suggesting limited feasibility and acceptability of depression screening in antenatal clinics. Conversely, evidence from the United Kingdom [15] and Sri Lanka [16] showed that midwives considered screening for depression in antenatal clinics as feasible and acceptable. In this study, feasibility refers to a process of determining whether an intervention can be shaped to be relevant and sustainable by identifying what aspects need modification and how changes might occur [17].…”
Section: Introductionmentioning
confidence: 99%